Uji Toksisitas Ekstrak Etanol Daun Tanaman Tembakau (Nicotiana tabacum L.) - Puji Prastowo; Selvia Dewi Pohan; Khairiza Lubis (Universitas Negeri Medan, 2016)
Tobacco (Nicotiana tabacum L.) was a popular plant, usually used as cigarette material, traditional medicine, chewy tobacco and natural insecticide. This study aims to investigate toxicity effects of tobacco to mice (Mus musculus). The study had been done from March to July 2015 in Plant Physiology Laboratory of Mathematic and Natural Sciences Unimed and Phatology Laboratory USU. The study used male mice as the animal test. Twenty-five mices were divided in to 5 groups. One control group and four groups were given the ethanolic extracts of tobacco in four doses 10%; 15%; 20%; dan 25% orally. Evaluation of toxic effects was 24 hours until 3 days after administration. Evaluation included physical and physiological adverse, behaviour changes, and histopathologycal adverse of liver and kidney. According to the results of study, ethanolic extract of tobacco made a systemic toxicity. Most of doses (except control) caused acute toxicity symptoms and immediately death to the tested animals. It affected mices in physic, behaviour and anatomy. The toxic symptoms were uncontrolable movement, aggressivity, tail abnormality, coordination damages, pupil extention, and refflects damages. Another effects were gastric, intestinal and testis inflammations. The liver and kidney were highly susceptible to toxicant. Histopathologycal examination showed that toxic affected congestion and necrosis in liver and kidney. Keywords: ethanol extract, toxicity, tobacco, histopathology, mice